Banking Competition, Institutional Investors and Financial Constraints: Evidence from Europe (2019)
This study analyzes the relationship between banking concentration, institutional investors and their impact on financial constraints across 27 equity markets in Europe for the period 2000-2015. Financial constraints are consequence of market failures due to the presence of asymmetric information among stakeholders/blockholders, where risk taking and investment choices are affected. Firm capital structure decisions rely on less cost-informative sources of external borrowing making corporate investment dependent to internal funds or projected cash flows. Bank competition and presence of institutional investors might play a central role in reducing firm financial constrains The results show that according to the information hypothesis, bank concentration reduces financial constraints, measured as the sensitivity of the investment to cash flows. However, this effect is mitigated to the extent that institutional investors have a greater equity-holdings which is consistent with a potential resource competition for reducing agency costs. The results are robust by analyzing different sources of heterogeneity. We include the heterogeneity at the institutional investor type i.e., grey versus independent, firm size and opacity. Our findings suggest that the investors of the independent type are the ones that would diminish the financial restrictions of the firms, and that the smaller, less opaque companies will replicate the results found in the base scenario.